Monitoring Smart Sustainable Cities: Business Intelligence approach to Smart Sustainable Cities - Charneira, Nuno Miguel Valentim (2022)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence